Does Obesity Aggravate Climacteric Symptoms in Postmenopausal Women? - Costa, Juliene Gonçalves; Rodrigues, Raquel Moreira; Puga, Guilherme Morais; Cheik, Nádia Carla (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To determine if there is a correlation between body mass index (BMI) and climacteric symptoms in postmenopausal women.Methods The study sample was composed of 109 postmenopausal women with a mean age of 57 ±  8 years, mean body mass index (BMI) of 30 ±  6 kg/m2, and 8 ±  8 years after menopause. For the assessment of the climacteric symptoms, the Blatt-Kupperman Index (BKI), the Menopause Rating Scale (MRS), and the Cervantes Scale (CS) were used. Data analysis was performed through the Chi-squared test, analysis of variance (ANOVA) with the Bonferroni post hoc test, and multiple linear regression. The level of significance adopted was of p < 0.05. The statistical analyses were performed using the Statistical Package for the Social Sciences (IBM SPSS Statistics for Windows, IBM Corp., Armonk, NY, United States) software, version 26.0.Results The multiple linear regression showed a positive association (p < 0.01) between BMI values and menopause symptoms when adjusted for age and time after menopause in the 3 questionnaires used (BKI: B = 0.432; CS: B = 304; and MRS: B = 302). Regarding symptom scores, the obese women had higher mean scores (p < 0.05) when compared to eutrophic women (BKI = 28 ±  10 and 20 ±  10; and MRS = 20 ±  10 and 13 ±  7, respectively). In the Chi-squared analysis, 28% of obese women had severe symptoms and 46% had moderate symptoms, while only 1% and 46% of eutrophic women had these same symptoms.Conclusion There is an association between BMI and climacteric symptoms, and overweight or obese women have more intense and moderate symptoms than eutrophic women.
Keywords: climacteric symptoms; obesity; overweight; menopause